18F-NaF PET/CT in Presumed Aseptic Pseudarthrosis after Spinal Fusion: Correlation with Findings at Revision Surgery and Intraoperative Cultures - Yacine El Yaagoubi; Jean-Edouard Loret; Eric Lioret; Clément Thomas; Adrien Simonneau; Laurent Vinikoff; Caroline Prunier-Aesch; Alain Chetanneau; Laurent Philippe; Maja Ogielska; Louis Bernard (World Journal of Nuclear Medicine)
Background Conventional imaging is useful to assess interbody fusion by showing complete trabecular bony bridging, but has a low positive predictive value for pseudarthrosis. Because alterations of bone metabolism may precede structural anatomical changes on computed tomography (CT), we aimed to investigate the ability of fluorine 18 sodium fluoride positron emission tomography/computed tomography (18F-NaF PET/CT) to identify pseudarthrosis after spinal fusion using surgical revision as the reference standard. Methods We retrospectively reviewed 18F-NaF PET/CT scans performed between February 2019 and September 2020 in patients experiencing pain after spinal fusion. We included the 18 patients who underwent revision surgery for suspicion of pseudarthrosis. Five consecutive patients who were clearly fused on CT served as the control group. Results In the revision surgery group (n=18), visual assessment by 18F-NaF PET/CT revealed that all 22 cages with an increased 18F-NaF uptake around intercorporal fusion material had mobility at revision surgery, whereas none of the fused patients (n=5) showed uptake around cage/intervertebral disk space. Among the 18 patients with presumed aseptic pseudarthrosis, intraoperative cultures revealed surgical site infection (SSI) caused by Cutibacterium acnes (C. acnes) in seven patients (38.9%). There was a statistically significant difference in standardized uptake values and uptake ratios between the revision surgery and control groups (p=5.3× 10−6 and p=0.0002, respectively). Conclusions 18F-NaF PET/CT imaging appeared as a useful tool to identify pseudarthrosis following spinal fusion. The unexpectedly high prevalence (38.9%) of SSI caused by C. acnes found in presumed aseptic patients supports the utility of intraoperative cultures in revision cases for pseudarthrosis, even without preoperative clinical suspicion of SSI.